Electrochemical characterization and application of carbon nanotubes and metal oxide nanoparticle modified electrodes. - Zidan, Mohammed (2011)
The modified glassy carbon electrodes by adhered microcrystals of bismuth oxide (Bi2O3) and zinc oxide (ZnO) has been studied extensively in characterization and application of these modified electrodes in mediating some selected compounds such as ascorbic acid and paracetamol in the presence of aqueous electrolytes. It is evident that the use of a lithium doped Bismuth oxide and multi-walled carbon nanotubes (MWCNT) modified glassy carbon electrode (Bi2O3/Li+/CNT/GC) tends to enhance the oxidation current of ascorbic acid during cyclic voltammetry compared to bare GC and (Bi2O3 /Li+/CNT) modified electrode. Peak potential was observed to shift slightly to less positive value by about 220mV and current was significantly hanced by about two folds. Under conditions of cyclic voltammetry, the sensitivity of the current is significantly dependent on pH, temperature, and electrolyte and scan rate. The result of scanning electron micrograph shows that the size increased slightly from 1 – 4 μm after electrolysis using Bi2O3/Li+/CNT modified electrode. The detection limit of this modified electrode was found to be 50M. The oxidation current of ascorbic acid decreased sharply after the first cycle and became stable with minor decreases after second cycle. It is therefore apparent that the Bi2O3 /Li+/CNT modified GC electrode possesses some degree of stability. During cyclic voltammetry, an oxidation peak of paracetamol appearing at +6.11 V vs.Ag/AgCl was observed. Enhance the oxidation current of paracetamol compared to bare GC and (Bi2O3/Li+/CNT) modified electrode. Peak potential was observed to shift slightly to less positive value by about 220 mV and current was significantly enhanced by about 3.2 folds. The sensitivity under conditions of cyclic voltammetry is significantly dependent on pH, temperature, and scan rate. Calibration plot reveals linearity from the range 5.0 x 10-7 to 2 x 10-3M with a correlation coefficient of 0.998. The detection limit was estimated to be 7.4 x 10-7 M. The usefulness of zinc oxide (ZnO) modificed of a glassy carbon (GC) electrode was extended in mediatig the oxidation of ascorbic acid in 0.1 M KH2PO4 electrolyte solution by cyclic voltammetry (CV). ZnO/GC electrode exhibited obvious enhancing and electrocatalyzing effect as it causes the oxidationcurrent of ascorbic acid to increase by 1.5 times as compared to bare GC electrode. The variation of scan rate study shows that the system undergoes diffusion-controlled process. Diffusion coefficient and rate constant of ascorbic acid were determined using hydrodynamic method (rotation disk electrode) with values of 5.4 x 10-6 cm2 s-1 and 2.5 x 10-3cm s-1 respectively for unmodified electrode, while the values of diffusion coefficient and rate constant of ascorbic acid using ZnO/GC electrode were 5.7 x 10-6 cm2 s-1 and 2.1x10-3cm s-1 respectively. Zinc oxide (ZnO) microparticles have been mechanically attached on the surface of a glassy carbon (GC) electrode and the effect on oxidation of paracetamol in 0.1 M KH2PO4 electrolyte solution by cyclic voltammetry (CV). Peak potential was observed to shift slightly to less positive value by about 150 mV and current was significantly enhanced by about 1.1 folds as compared to bare GC electrode. In addition, calibration plot reveals linearity from the range 2.0 × 10−5 to 5.0 × 10−3 M with a correlation coefficient of 0.997. Also evident that use of MgB2/Li+/CNT/GC modified electrode tends to enhance the oxidation of paracetamol in 0.1 M KH2PO4 supporting electrolyte at pH 4.2 at bare (unmodified) GC electrode, MgB2/GC modified electrode, MgB2/Li+/GC modified electrode and MgB2/Li+/CNT/GC modified electrode. While at the modified GC electrode, peak shift of 130 mV and 150 mV towards less positive region was observed for MgB2/Li+/CNT/GC and MgB2/Li+/GC respectively with a slight current increase as compared to those of an unmodified electrode. However, at MgB2/Li+/CNT/GC current increased by 3 times with a similar peak shift as those of MgB2/Li+/GCE, indicating presence of a electrocatalysis process effected by the MgB2/Li+, and MgB2/Li+/CNT coating.